Bioavailability of Melatonin after Administration of an Oral Prolonged-Release Tablet and an Immediate-Release Sublingual Spray in Healthy Male Volunteers - Samira Ait Abdellah; Véronique Raverot; Caroline Gal; Isabelle Guinobert; Valérie Bardot; Claude Blondeau; Bruno Claustrat (Adis, Springer Healthcare, 2023)
Abstract Background The benefit of exogenous melatonin is based on its bioavailability, which depends on the galenic form, the route of administration, the dosage, and the individual absorption and rate of hepatic metabolism. Objective The objective of this study is to investigate the bioavailability of melatonin after administration of an oral prolonged-release tablet (PR form) and an immediate-release sublingual spray (IR form). The main metabolite of melatonin, 6-sulfatoxymelatonin (6-SMT), was also measured, which has not been done in previous studies. Its determination is important as an index of the hepatic transformation of melatonin. Methods In this single-center, open-label, randomized, crossover study, 14 healthy male volunteers received one tablet of the PR form (1.9 mg melatonin) or two sprays of the IR form (1 mg melatonin) during two visits separated by a washout period. Blood samples were collected over 7 and 9 h for the IR and PR form, respectively, to determine the main pharmacokinetic parameters. Results The observed kinetics were consistent with those expected for immediate and prolonged-release forms. Pulverization of the spray resulted in an early, high plasma melatonin peak (C max: 2332 ± 950 pg/mL; T max: 23.3 ± 6.5 min), whereas tablet intake produced a lower peak (C max: 1151 ± 565 pg/mL; T max: 64.2 ± 44.2 min; p < 0.001 for comparison of C max and T max) followed by a plasma melatonin plateau and a more prolonged decay over time. Plasma melatonin/6-SMT AUC0-540/420 ratio was 0.09 for the PR form and 0.16 for the IR form. Both galenic forms were well tolerated. Conclusions The results suggest that the galenic forms containing melatonin assessed in this study are suitable for the treatment of certain sleep disorders such as sleep onset delay and transient nocturnal awakenings for the IR form and insomnia for the PR form. Trial Registry Registration number: NCT04574141.